Acceptance level and influencing factors of advance care planning among patients with schizophrenia in China: a cross-sectional survey - Liang, Shicong; Huang, Lei; Tang, Shu-Tong; Li, Hong-Xing; Huang, Jia-Wei; Zhou, Wen-Qing; Xia, Zhi-Chun (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to explore the current acceptance of advance care planning (ACP) among patients with schizophrenia and investigate the influencing factors.MethodsA cross-sectional study was conducted from September 2023 to January 2024 using a convenience sampling method. A total of 225 patients with schizophrenia were selected from a Grade A, Class III Psychiatric Hospital and the Department of Psychiatry of a Grade A, Class III General Hospital in Guangzhou, China. The Advance Care Planning Readiness Scale, the Chinese version of the Brief Neurocognitive Test Battery(C-BCT), the Brief Psychiatric Rating Scale(BPRS), and the Medication Adherence Questionnaire(MAQ) were used to survey the patients with schizophrenia.ResultsMean ACP readiness score was 84.76 ± 11.97, with 55.6% showing high acceptance. Readiness positively correlated with age (r=0.161, p=0.021) and hospitalization frequency (r=0.235, p=0.001), and negatively with symptom severity (r=-0.159, p=0.022). Patients with comorbidities (p=0.001) or personal/family health crises (p=0.033) had higher readiness. Regression analysis identified cognitive impairment, religious beliefs, hospitalization frequency, and medication adherence as key predictors (R²=0.118, p<0.001), explaining 11.8% of variance.ConclusionsSchizophrenia patients demonstrate higher than average ACP acceptance, with 55.6% of the patients showing a high level of acceptance. Improved medication adherence, frequent hospitalizations, religious beliefs and reduced thinking disorder severity. Culturally sensitive health education is recommended to facilitate ACP discussions in clinical practice.